Preparation and characterization of a novel highly hydrophilic and antifouling polysulfone/nanoporous TiO2 nanocomposite membrane. (8th September 2016) - Bidsorkhi, H Cheraghi; Riazi, H; Emadzadeh, D; Ghanbari, M; Matsuura, T; Lau, W J; Ismail, A F
Abstract: In this research, novel ultrafiltration nanocomposite membranes were prepared by incorporating self-synthesized nanoporous titanium dioxide (NTiO2 ) nanoparticles into polysulfone. The surface of the nanoparticle was treated with a silane-based modifier to improve its distribution in the host polymer. Atomic-force microscopy, scanning electron microscopy, Fourier transform infrared spectroscopy, Brunauer–Emmett–Teller, transmission electron microscopy, energy-dispersive x-ray spectroscopy, porosity and contact angle tests were conducted to characterize the properties of the particles as well as the fabricated nanocomposite membranes. The effects of the nanoparticle incorporation were evaluated by conducting ultrafiltration experiments. It was reported that the membrane pure water flux was increased with increasing NTiO2 loading owing to the high porosity of the nanoparticles embedded and/or formation of enlarged pores upon addition of them. The antifouling capacity of the membranes was also tested by ultrafiltration of bovine serum albumin fouling solution. It was found that both water flux and antifouling capacity tended to reach desired level if the NTiO2 added was at optimized loading.